2023
DOI: 10.22342/jme.v14i2.pp253-274
|View full text |Cite
|
Sign up to set email alerts
|

Web-based realistic mathematics learning environment for 21st-century skills in primary school students

Abstract: This study aims to develop a valid, practical, and which has potential effect web-based realistic mathematics learning environment with the six cultural contexts of the island of Sumatera. The learning environment has the potential to positively impact primary school students. The study employed design research method, which encompassed the preliminary, design, and assessment stages using the Kirkpatrick model. The research subjects consisted of three model teachers and 57 fourth-grade students. Research data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…The development results of this research confirmed that the previous researches conducted by Lin et al [26], Azid et al [27], and Aboraya [28] stated that web-based learning could be implemented in class and improve students' mathematical achievement and problem-solving skills. In addition, Le Phicon et al [29], Sugiharni et al [30], and Lisnani et al [31] emphasized that a web-based learning environment supports students' learning process and positively affects mathematics teaching and learning. Moreover, Kefalis & Drigas [32] explained that through a web-based application, communication between students and teachers becomes synchronized, thus encouraging collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…The development results of this research confirmed that the previous researches conducted by Lin et al [26], Azid et al [27], and Aboraya [28] stated that web-based learning could be implemented in class and improve students' mathematical achievement and problem-solving skills. In addition, Le Phicon et al [29], Sugiharni et al [30], and Lisnani et al [31] emphasized that a web-based learning environment supports students' learning process and positively affects mathematics teaching and learning. Moreover, Kefalis & Drigas [32] explained that through a web-based application, communication between students and teachers becomes synchronized, thus encouraging collaboration.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the development of comics packaged in grammatic books has also been proven to improve the creative thinking skills of grade IV elementary school students (Risma et al, 2022). Thus, using comics as a learning medium can be considered an effective strategy to improve students' creative thinking skills at various levels of education (Lisnani et al, 2023).…”
Section: Creative Thinkingmentioning
confidence: 99%
“…Additionally, the three models described above were developed in secondary schools and colleges, while learning models aimed at improving mathematical literacy have yet to be developed in elementary schools. Aside from learning models, other products such as web-based RME (Lisnani et al, 2023) and learning modules based on RME (Aulia & Prahmana, 2022;Mattoliang et al, 2022;Yuliana et al, 2023) have also shown effectiveness in increasing students' mathematical literacy.…”
Section: Product Testing Stagementioning
confidence: 99%